Identifikasi Perilaku Petani Cabai Merah Keriting dalam Menghadapi Risiko Produksi di Desa Sumberejo, Kecamatan Ngablak, Kabupaten Magelang - Deprianto Sembiring; Yuliawati Yuliawati (Universitas Tidar, 2026)
Curly red chili farming faces high production risks caused by weather changes, pests and diseases, and uncertainty in the use of production inputs. This study aimed to identify farmers’ behavior in facing production risks in Sumberejo Village, Ngablak District, Magelang Regency. The research used a quantitative descriptive approach with 30 respondents selected through simple random sampling. Data were analyzed using the Cobb-Douglas production function and the Moscardi and de Janvry model through the K(S) parameter approach. The results revealed that most farmers were classified as risk averse (43.3%), followed by risk neutral (40%) and risk lover (13.3%), while 3.3% of respondents could not be classified because their K(S) values were outside the model classification range. These findings indicate that curly red chili farmers tend to be cautious in making production decisions to reduce the risk of income instability.